PERKEMBANGAN KURIKULUM PENDIDIKAN DI INDONESIA DALAM PERSPEKTIF KEBIJAKAN PUBLIK - Wicaksono, Juniaris Agung (Ngabari: Jurnal Studi Islam dan Sosial, 2018)
The curriculum has been around since ancient Greece, defined an education curriculum is program provided by educational institutions. Based on education program, students carry out various learning activities that have an impact on encouragment toward their development and growth in accordance with their goals. The education system has been established with Law No. 20 of 2003 as its legal basis. In its development education in Indonesia used at least four basic strategies, first; equity of opportunity to obtain education, second; the relevance of education, third; improving the quality of education, and fourth; the efficiency of education. Based on the history of curriculum policy, can be seen that practical education in Indonesia is inseparable from testing. Policies are easy to change, only based on short-term thinking, finally the practical curriculum almost changes every ten years.